An Evaluation of Academic Information System Success at Widyatama University Using the DeLone and McLean Model - Isak Ramlan; Muchamad Rusdan (LP2M Universitas Widyatama, 2025)
The Academic Information System (AIS) is the backbone of operations and services in modern higher education. Evaluating the quality of AIS is crucial to ensure satisfaction and its success in supporting academic activities. This study aims to evaluate the quality of SIAKAD-UTama using the DeLone & McLean Model. The DMM identifies six dimensions of information system success System Quality, Information Quality, Service Quality, Use, User Satisfaction, and Net Benefits. The study employed a quantitative approach, using a survey of 200 respondents who were SIAKAD-UTama users. Data were analyzed using Partial Least Squares Structural Equation Modeling using SmartPLS 4.0. The results of the measurement model analysis indicated that all constructs met the requirements for convergent validity (AVE > 0.50) and reliability (CR > 0.70). The results of the structural model analysis show that Information Quality has the most significant influence on User Satisfaction β = 0.387; p = 0.000 and Use β = 0.298; p = 0.002. System Quality has a significant influence on User Satisfaction β = 0.215; p = 0.014 but not significant on Use β = 0.156; p = 0.069. Service Quality also has a significant influence on User Satisfaction β = 0.178; p = 0.045. There is a significant relationship between Use and User Satisfaction. Both User Satisfaction β = 0.356; p = 0.000 and Use β = 0.289; p = 0.001 significantly influenced Net Benefits. The results of this study provide insight for Widyatama University to optimize AIS by prioritizing improving Information Quality to increase satisfaction, utilization, and benefits for the academic community.